THE PROBABILITY DENSITY LOCATION OF LIGHT AIRCRAFT WITHIN AIRPORT AND THEIR DISTRIBUTION FROM RUNWAY - Государська, І. (Proceedings of National Aviation University (archive), 2012)
The accident locations of light aircraft with take-off weight less 4 tones were collected. Statistical data were taken from ADREP (ІСАО), NTSB, ALPA, Aіrclaіms, CAA-UK, ASRS, AІDS databases for 30 year period. Dynamics of accident rate was represented for light aircraft in republics of participants Agreement of civil aviation (including Ukraine) for period from 1982 to 2009. Distributions of location of the light aircraft accident from runway end were determined. Bivariate and three-dimensional distributions of location of light aircraft accident within airports were found